Media e-komik strip “gege & gizi” terhadap pengetahuan dan sikap remaja tentang gizi seimbang - Diastuti, Putri Permata; Hardini, Deisy Sri (Holistik Jurnal Kesehatan, 2025)
Background: Improper implementation of balanced nutrition is a major problem that occurs among adolescents. Nutritional problems in adolescents can arise due to incorrect attitudes or eating patterns. Inadequate nutritional fulfillment with nutritional intake below the recommended normal. While excessive nutrition is caused by nutrition that exceeds normal. Purpose: To determine the effect of the comic strip "gege & gizi" on adolescents' knowledge and attitudes about balanced nutrition. Method: This quantitative quasi-experimental study used a pretest-posttest design with a control group. The study was conducted on 80 10th-grade students at Purwokerto State Senior High School 3. Data analysis used univariate and bivariate paired t-tests. Results: The majority of respondents were aged 15-16, female, and severely underweight. Eleven respondents were in the intervention group and five respondents were in the control group. The mean knowledge and attitude scores of the intervention group before the comic strip were 5,050 and 30.70, respectively. After the intervention, these scores increased to 7,255 and 40.80, respectively. The mean knowledge and attitude scores of the control group before the treatment were 3.520 and 29.28, respectively. After the intervention, the number of respondents increased to 5,605 and 31.50, respectively. The level of knowledge and attitude of respondents in the intervention group improved after the treatment. Meanwhile, the control group, after receiving the treatment, remained in the "poor knowledge" category, but the number of respondents in the "adequate" category increased. Conclusion: Electronic comic strips are effective in improving knowledge and attitudes about implementing a balanced diet (p-value 0.000).   Keywords: Attitude; Balanced Nutrition; E-Comic Strip; Knowledge; Teenagers.   Pendahuluan: Penerapan gizi seimbang yang tidak tepat menjadi masalah utama yang terjadi di kalangan remaja. Persoalan gizi pada remaja muncul dapat disebabkan oleh sikap atau pola makan yang keliru. Pemenuhan gizi yang kurang diakibatkan oleh asupan gizi dibawah normal yang sudah dianjurkan. Sedangkan gizi yang berlebih diakibatkan oleh gizi yang melebihi normal. Tujuan: Untuk mengetahui pengaruh media e-komik strip “gege & gizi” terhadap pengetahuan dan sikap remaja tentang gizi seimbang. Metode: Penelitian kuantitatif quasy eksperiment dengan rancangan pretest-posttest with control group design. Penelitian dilakukan pada 80 siswa kelas 10, di SMA Negeri 3 Purwokerto. Analisis data menggunakan univariat dan bivariat paired t-test. Hasil: Responden penelitian ini mayoritas berusia 15-16 tahun, berjenis kelamin perempuan, berstatus gizi kurus tingkat berat di kelompok intervensi sebanyak 11 responden, di kelompok kontrol sebanyak 5 responden. Nilai rata-rata pengetahuan dan sikap kelompok intervensi sebelum diberikan perlakuan menggunakan media e-komik strip adalah 5.050 dan 30.70, setelah diberikan intervensi meningkat menjadi 7.255 dan 40.80. Nilai rata-rata pengetahuan dan sikap kelompok kontrol sebelum diberikan perlakuan adalah 3.520 dan 29.28, setelah intervensi menjadi 5.605 dan 31.50. Tingkat pengetahuan dan sikap responden kelompok intervensi setelah diberikan perlakuan meningkat. Sedangkan kelompok kontrol setelah diberikan perlakuan pada pengetahuan masih berada di kategori kurang, namun jumlah responden pada kategori cukup meningkat. Simpulan: Media e-komik strip berpengaruh dalam upaya meningkatkan pengetahuan dan sikap tentang penerapan gizi seimbang (p-value 0.000).   Kata Kunci: E-Komik Strip; Gizi Seimbang; Pengetahuan; Remaja; Sikap.